Pendampingan Pemanfaatan Mikroskop Digital dalam Konservasi Koleksi Kain Songket Museum Sultan Mahmud Badaruddin II - Shinta Puspasari; Rendra Gustriansyah; Ahmad Sanmorino; Ditho Hersilava; Ade Fathurahman (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Conservation of Palembang Songket woven cloth is carried out at SMBII Museum. The thread fibers woven into Songket cloth are small in size and require a microscope to see the thread fibers clearly before determining the appropriate conservation mechanism for fabric damage. Community service activities are carried out by assisting in the use of digital microscopes in the conservation of Songket cloth collections. A digital microscope is used to magnify the appearance of the gold thread fibers of the Songket cloth, whether there is damage or not. The activity began with setting up a digital microscope device to be used in the study of Songket cloth conservation and continued with assistance in using the microscope by participants. The results of the assistance show that users can easily use digital microscope devices to display Songket fabric fibers that are damaged and require conservation. Hopefully, this community service will make it easier for the SMBII museum to carry out conservation and learning tasks at the museum and have an impact on ensuring the resilience of the Palembang Songket cloth cultural heritage in the digital era.